Guidebook for selecting methods to monitor airport and aircraft deicing materials - Ervin, Mark.; Caudell, Dennis; National Research Council (U.S.). Transportation Research Board; Airport Cooperative Research Program; United States. Federal Aviation Administration; Gresham, Smith, and Partners; Terra Hydr, Inc. (Washington, D.C. : Transportation Research Board, 2012)
This report provides a step-by-step process for identifying, evaluating, and selecting methods to monitor storm water that is subject to runoff containing deicing materials. The guidance addresses identifying the parameters to be monitored and discusses the appropriateness of various monitoring methods and instrument types to meet an airport's specific needs. The guidebook also provides recommendations for setup, operation, and maintenance of each monitoring method. The guidebook also includes helpful appendices that define relevant technical terms and provide sample outreach materials to help communicate the selection process to nontechnical stakeholders. Technical information on various on-site monitoring methods is provided in a series of fact sheets. These fact sheets, which are organized by the parameter being monitored, describe key factors such as how the method works, its current level of adoption within the industry, implementation considerations, cost, and advantages/disadvantages.
At head of title: Airport Cooperative Research Program.
"Fact sheets. On-site monitoring methods #58-100"--Supplement.
Research sponsored by the Federal Aviation Administration
Includes bibliographical references (page 53).
Keywords: Airplanes -- Ice prevention -- Environmental aspects -- United States; Deicing chemicals -- Environmental aspects -- United States; Runoff -- Environmental aspects -- United States; Stormwater infiltration -- United States -- Management; Aeronautics -- Safety measures